Food and feeding habits of Clarias batrachus (Linnaeus, 1758) from Ambajogai, Maharashtra, India - Sakhare, Vishwas Balasaheb; Chalak, Ashvini Dnayndeo (Journal of Fisheries, 2014)
The food analysis of 150 specimens of Clarias batrachus revealed that the food consisted of insect larvae, small fish, shrimps and organic debris. Small fish and insect larvae were preferred as the primary food item in all the seasons. On average for all months of the study period, small fish dominated the list with a percentage of 30.27.The other food items in descending order are insect larvae (27.66%), worms (20.27%), shrimps (14.3%) and organic debris (7.05%).The feeding intensity in mature fishes was found to be very poor during August to September. This period of poor feeding activities in case mature fishes coincides with the peak spawning season.